The University in Pandemic: Impact of COVID-19 on Extension and Technology Transfer - Britto, Fabian Andrés (2022)
The activities of university extension and linkage and technology transfer deal with issues that  overlap  and  complement  each  other,  reflecting  the  involvement  of  the  university  with its socio-productive environment through the flow of knowledge and technologies. In the face of the COVID-19 pandemic, the measures initially adopted by the Argentine public management national universities involved a wide range of extension and transfer actions in response to the main demands that arose in the aforementioned situation of health emergency situation.In  this  context,  we  set  out  to  identify  the  main  changes  produced  in  the  exercise  of  the  third  university  mission,  referring  to  university-environment  collaboration  and  mainly known as extension, linkage or transfer. To do this, 3 universities with different characteristics related to their origin, historical background and territorial extension were selected: the National University of Río Negro, the National University of Quilmes and the National University of La Plata.